PBC Approach for SMES Devices in Electric Distribution Networks (2018)
This express brief presents a nonlinear active and reactive power control for a superconducting magnetic energy storage (SMES) system connected in three-phase distribution networks using pulse-width modulated current-source converter (PWM-CSC). The passivity-based control (PBC) theory is selected as a nonlinear control technique, since the open-loop dynamical model exhibits a port-Hamiltonian (pH) structure. The PBC theory exploits the pH structure of the open-loop dynamical system to design a general control law, which preserves the passive structure in closed-loop via interconnection and damping reassignment. Additionally, the PBC theory guarantees globally asymptotically stability in the sense of Lyapunov for the closed-loop dynamical system. Simulation results in a three-phase radial distribution network show the possibility to control the active and reactive power independently as well as the possibility to use the SMES system connected through a PWM-CSC as a dynamic power factor compensator for time-varying loads. All simulations are conducted in a MATLAB/ODE package. © 2004-2012 IEEE.